Le populisme climatique de Donald J. Trump et le libre marché des idées - Jean-Daniel Collomb (Transatlantica)
This article seeks to determine how relevant the notion of populism is to illuminate Donald Trump’s stance on climate change thanks to an analysis of his public statements regarding this issue. Donald Trump’s climate populism is defined as a rejection of the authority of intellectual, media and scientific elites in the name of the ability of ordinary people to decide for themselves and in defense of their material well-being. Further, the article shows that Donald Trump uses all the forms of climate skepticism which have been identified by social scientists. In addition, the article demonstrates that the current political and media environment in the United States reinforces climate populism.